Analysis of the implementation of Johannesburg inner city renewal strategies. - Nkokoto, Mokela (My University, 2007)
This paper is a report on the research undertaken to evaluate the implementation of the Urban Renewal strategies that the City of Johannesburg adopted for the CBD renewal through the Blue IQ. The study was restricted to the views expressed by the general community, business community, Johannesburg Development Agency (JDA). Johannesburg Housing Company (JHC), Blue IQ, Gauteng Development Agency and Gauteng Economic Development Agency (GEDA), which are the main role players in the CBD renewal effort. There was administered questioner to the members of the Business and general communities that were randomly picked using the fish bowl method. Interviews were conducted with the senior executive staff of JDA. Blue IQ, JHC. Statistics derived from the above company s websites was used as well. The results of the study show that the renewal strategy has been largely successful in so far as a number of factors, which have contributed to the CBD decay such as poor infrastructure and slumps. There have also been considerable efforts to address acute shortage of parking space by private partners such as financial institutions. Although crime has decreased it is still posing a serious challenge as most people still consider the CBD high risk. However there is still a room for improvement, which includes: the enhancement of safety and security, the infrastructure maintenance policy and the enforcement of the municipality by laws and town planning scheme. Overall the strategies have also improved the economic performance of the city significantly though unemployment still remain high with the ever increasing number of people coming to seek opportunities.
Student number: 0200613W Faculty of Engineering and the Built Environment Master of Property Development and Management.
Keywords: Renewal Strategy; CBD Renewal; Urban Renewal Strategies; CBD Decay; City of Johannesburg; Blue IQ; Johannesburg Development Agency (JDA); Johannesburg Housing Company (JHC); Gauteng Economic Development AAGency (GEDA); Infrastructure maintenance policy